Parasitic arthritis induced by Strongyloides stercoralis. - Akoğlu, T (1984)
A 40-year-old man presented with palpable purpura and symmetrical polyarticular arthritis. Histological examination of the synovial membrane and fluid unexpectedly disclosed Strongyloides stercoralis infestation of the ankle joint.